Simulating and modeling CO2 flux emitted from decomposed oil palm root cultivated at tropical peatland as affected by water content and residence time - Heru Bagus Pulunggono; Syva Fitriana; Desi Nadalia; Moh Zulfajrin; Lina Lathifah Nurazizah; Husni Mubarok; Nizam Tambusai; Syaiful Anwar; Supiandi Sabiham (Brawijaya University, 2022)
Determining the oil palm dead roots contribution to total (Rt) and heterotrophic (Rh) respiration as a source of greenhouse gas/GHG emission in tropical peatland is urgently required, as well as predicting their magnitude to cope with difficulties of direct in-situ measurement. This study is designed to simulate the CO2 flux emitted from oil palm dead roots/Rdr in tropical peatland as affected by water content/WC and residence time/RT. The dead oil palm roots were cleaned, treated with control/15, 100, 150, 300, and 450%WC, and then incubated for three months. CO2 flux measurement, C, N, and CN ratio determination were conducted every month. This study demonstrated the importance Rdr among other CO2 emission sources, ranging from 0.05-2.3 Mg CO2 ha-1 year-1 with an average of 0.7 Mg CO2 ha-1 year-1. Rdr contribution for literature Rt and Rh were around 0.3 to 1.3 and 0.9 to 3.5%, respectively. As a product of microbial respiration, Rdr was affected by WC and RT, supported by analysis of variance, linear mixed effect model/REML, and multivariate analysis. 100-150%WC resulting in significant and highest Rdr, whereas the increase (300-450%WC) or decrease (15%WC) would generate lower emission. Rdr culminated in the first month after incubation; meanwhile, it declined in the following months. This study also emphasized non-linear relationships between CO2 flux and other root properties, which can be modeled conveniently using non-linear approach, particularly using polynomial and artificial intelligence-based models. The simulation presented in this study served as an initial attempt to separate Rdr from Rh, as well as to predict CO2 flux with reasonable accuracy and interpretable methods.